Psychosocial Intervention With or Without Antipsychotic Medication for First-Episode Psychosis: A Randomized Noninferiority Clinical Trial. Issue 1 (20th March 2020) - Francey, Shona M; O'Donoghue, Brian; Nelson, Barnaby; Graham, Jessica; Baldwin, Lara; Yuen, Hok Pan; Kerr, Melissa J; Ratheesh, Aswin; Allott, Kelly; Alvarez-Jimenez, Mario; Fornito, Alex; Harrigan, Susy; et al.
Abstract: This triple-blind (participants, clinicians, and researchers) randomized controlled noninferiority trial examined whether intensive psychosocial intervention (cognitive-behavioral case management, CBCM) for first-episode psychosis (FEP) in 15–25 year-olds managed in a specialized early intervention for psychosis service was noninferior to usual treatment of antipsychotic medication plus CBCM delivered during the first 6 months of treatment. To maximize safety, participants were required to have low levels of suicidality and aggression, a duration of untreated psychosis (DUP) of less than 6 months, and be living in stable accommodation with social support. The primary outcome was level of functioning as assessed by the Social and Occupational Functioning Scale (SOFAS) at 6 months. Ninety young people were randomized by computer, 46 to placebo, and 44 antipsychotic medication and 33% of those who commenced trial medication completed the entire 6-month trial period. On the SOFAS, both groups improved, and group differences were small and clinically trivial, indicating that treatment with placebo medication was no less effective than conventional antipsychotic treatment (mean difference = −0.2, 2-sided 95% confidence interval = −7.5 to 7.0, t = 0.060, P = .95). Within the context of a specialized early intervention service, and with a short DUP, the immediate introduction of antipsychotic medication may not be required for all cases of FEP in order to see functional improvement. However, this finding can only be generalized to a very small proportion of FEP cases at this stage, and a larger trial is required to clarify whether antipsychotic-free treatment can be recommended for specific subgroups of those with FEP. Trial Registration: ACTRN12607000608460 (www.anzctr.org.au ).